Surface wipe and bulk sampling of household dust: arsenic exposure in Cornwall, UK. Issue 3 (1st February 2018) - Middleton, D. R. S.; Watts, M. J.; Hamilton, E. M.; Coe, J. D.; Fletcher, T.; Crabbe, H.; Close, R.; Leonardi, G. S.; Polya, D. A.
Abstract : Dust elemental levels can be expressed as concentrations (bulk samples) or surface loadings (wipe samples). Abstract : Dust elemental levels can be expressed as concentrations (bulk samples) or surface loadings (wipe samples). Wipe sampling has not been widely adopted for elements other than lead (Pb). In this study, 433 wipe samples from 130 households in south west England – a region of widespread, natural and anthropogenic arsenic contamination linked with previous mining activities-were analysed to (i) quantify loadings of arsenic (As); (ii) assess the quality of wipe data using QA/QC criteria; (iii) estimate, using published ingestion rates, human exposure to As in dust using loadings and concentrations from 97 bulk samples and (iv) comparatively assess the performance of wipe and bulk sampling using associations with As biomonitoring data (urine, toenails and hair). Good QC performance was observed for wipes: strong agreement between field duplicates, non-detectable contamination of field blank wipes and good reference material recoveries. Arsenic loadings exceeded an existing urban background benchmark in 67 (52%) households. No exceedances of tolerable daily As intake were observed for adult exposure estimates but infant estimates exceeded for 1 household. Infant estimates calculated using bulk concentrations resulted in 4 (3%) exceedances. Neither wipe nor bulk As metrics were sufficiently better predictors of As in biospecimens. Sampling strategies, analytical protocols, exposure metrics and assessment criteria require refinement to validate dust sampling methodologies.